Synovial Fluid Lubrication: The Effect of Protein Interactions on Adsorbed and Lubricating Films. (March 2015) - Parkes, Maria; Myant, Connor; Cann, Philippa M.; Wong, Janet S.S.
Abstract: Synovial fluid lubrication is dependent on protective protein films that form between joint surfaces. Under static conditions surface film formation occurs through adsorption, while under dynamic conditions protein aggregation under shear and load becomes the dominant mechanism. This work examines how the protein content of six model synovial fluids affects film formation under static and rolling conditions and if the changes in properties can be correlated. With an increase in the statically adsorbed mass and the rate of adsorption the film thickness under rolling increased. These increases did not correlate with the total protein content of the fluid, but were dependent on the type of protein. An increase in pH reduced the adsorbed mass, rate of adsorption and film thickness, but was of secondary importance to the type of protein. The rolling film thickness was also correlated with the viscoelastic properties of the films formed under static conditions. In this case thinner rolling films corresponded to the more hydrated, viscoelastic adsorbed films. The strong correlations found between the properties of the adsorbed films and those formed under rolling indicate that the same protein–protein and protein–surface interactions may govern both mechanisms of film formation despite the differences in the film structures.